Desenvolvimento e validação de conteúdo de aplicativo móvel para o controle do HIV/AIDS - GAIA, Melyane de Assunção (Universidade Federal do Pará, 2023)
HIV/AIDS is a global health prblem and the northern region of Brazil has stood out with the increase in new cases and high morbidity and mortality throughout the country. Since the decentralization of HIV diagnosis to primary health care (PHC), has gained autonomy in its workflow, which requires a significant technological arsenal for the planning, organization, and operationalization of services. Although an Information and Communication (ICT) usability application is a powerful tool for engagement and health promotion, there is still no application aimed at the mobile nurse's HIV/AIDS workflow. This, the present study as a research question “What is the validity of the content of the content for an application that can mediate the assistance of nurses to people living with HIV?”. OBJECTIVE: To develop the content of a valid mobile media application for health promotion, prevention of HIV infection. METHOD: this is a methodological study for the elaboration and validation of content for a mobile application